1994
DOI: 10.1161/01.str.25.10.1915
|View full text |Cite
|
Sign up to set email alerts
|

Dementia after stroke is a predictor of long-term survival.

Abstract: Background and Purpose The aim of this study was to determine whether dementia after stroke adversely influences long-term survival.Methods Subjects were 251 patients >60 years of age with ischemic stroke who were given neurological, neuropsychological, and functional examinations 3 months after hospitalization and were followed up prospectively. Using criteria modified from the Diagnostic and Statistical Manual of Mental Disorders-III-R, dementia was found in 66 (26.3%) patients at the 3-month baseline examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
2
9

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 28 publications
4
134
2
9
Order By: Relevance
“…According to the result of this study, it was found that the memory disturbance between 20 -80 percentage 7,8 and the incidence of dementia after stroking was 5 -48%. 3,4,[11][12][13][14][15][16] Moreover, the incident of dementia after recurrent stroke was 33.33 %.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…According to the result of this study, it was found that the memory disturbance between 20 -80 percentage 7,8 and the incidence of dementia after stroking was 5 -48%. 3,4,[11][12][13][14][15][16] Moreover, the incident of dementia after recurrent stroke was 33.33 %.…”
Section: Discussionmentioning
confidence: 68%
“…4 From the previous study that traced patients with stroke during three months it was found that most patients have mild disability (57.2%), some have severe disability (18.6%), and a few have moderate disability (9.4%). 5 In addition, stroke also led to memory disturbance and dementia over 9.4 times compared with and without stroke, 6 memory disturbance between 20 -80 percentage, 7,8 and the incidence of dementia was 5-48 percentage. 3,4 Moreover, probability of recurrent stroke increased, 9,10 recurrent stroke was 33.3 percentage, 11 the mortality rate of dementia after stroking was three times compared with and without, 7 and the estimated cost of caring the dementia patients around the world is approximately 604,000 million US dollar.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because PSD has been associated with recurrent vascular events 4 and death, 7 we hypothesize that a similar association may exist with CIND severity and outcomes after stroke.…”
mentioning
confidence: 95%
“…El deterioro cognitivo secundario a un ictus se asocia con una mayor mortalidad (Tatemichi et al, 1994), mayor tasa de institucionalización (Pasquini, Leys, Rousseaux, Pasquier, y Henon, 2007) y un aumento en los costes sanitarios (Claesson, Linden, Skoog, y Blomstrand, 2005). Reducir el impacto de la HVE en la capacidad funcional del paciente debe ser uno de los objetivos de la rehabilitación del ictus ya que influye directamente en su calidad de vida, así como la de sus cuidadores.…”
Section: Conclusionesunclassified